Genotoxicity and Fetal Abnormality in Streptozotocin-Induced Diabetic Rats Exposed to Cigarette Smoke Prior to and during Pregnancy - Damasceno, Débora Cristina [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Sinzato, Y. K. [UNESP]; Lima, P. H. O. [UNESP]; Souza, M. S. S. [UNESP]; Iessi, I. L. [UNESP]; Kiss, A. C. I. [UNESP]; Takaku, M. [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (Johann Ambrosius Barth Verlag Medizinverlage Heidelberg Gmbh, 2011)
Background: Maternal hyperglycemia during early pregnancy is associated with increased risk of abnormalities in the off spring. Malformation rates among the off spring of diabetic mothers are 2-5-fold higher than that of the normal population, and congenital malformations are the major cause of mortality and morbidity in the off spring of diabetic mothers. Metabolic changes, such as hyperglycemia and the metabolites obtained from cigarettes both increase the production of reactive oxygen species (ROS) in the embryo or fetus, causing DNA damage.Objective: To evaluate the maternal and fetal genotoxicity, and to assess the incidence of fetal anomaly in diabetic female rats exposed to cigarette smoke at different stages of pregnancy in rats.Material and Method: Diabetes was induced by streptozotocin administration and cigarette smoke exposure was produced by a mechanical smoking device that generated mainstream smoke that was delivered into a chamber. Female Wistar rats were randomly assigned to: non-diabetic (ND) and diabetic (D) groups exposed to filtered air; a diabetic group exposed to cigarette smoke prior to and during pregnancy (DS) and a diabetic group only exposed to cigarette smoke prior to pregnancy (DSPP). on pregnancy day 21, blood samples were obtained for DNA damage analysis and fetuses were collected for congenital anomaly assessment. Statistical significance was set at p<0.05 for all analysis.Results and Conclusion: Exposure of diabetic rats to tobacco smoke prior to pregnancy increased fetal DNA damage, but failed to induce teratogenicity. Thus, these results reinforce the importance for women to avoid exposure to cigarette smoke long before they become pregnant.
Keywords: diabetes; cigarette smoke; pregnancy; genotoxicity; fetal anomaly; rat